2014
DOI: 10.3109/07435800.2014.895377
|View full text |Cite
|
Sign up to set email alerts
|

3βHSD and CYB5A double positive adrenocortical cells during adrenal development/aging

Abstract: Androstenedione is a common precursor of sex steroids produced and secreted in the human adrenal gland and produced by 3β-hydroxysteroid dehydrogenase (3βHSD), 17α-hydroxylase/17-20 lyase (CYP17) and cytochrome b5 (CYB5A). 3βHSD is expressed in the zona glomerulosa (ZG) and fasciculata (ZF), CYP17 in the ZF and zona reticularis (ZR) and CYB5A in the ZR, respectively. We previously demonstrated the presence of cortical parenchymal cells co-expressing 3βHSD and CYB5A with hybrid features of both ZF and ZR in hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 32 publications
(32 reference statements)
1
14
0
Order By: Relevance
“…In the normal adrenal gland, HSD3B2 and CYB5A are segregated to the zonae glomerulosa and fasciculata or the zona reticularis, respectively, such that the major adrenal C 19 steroids are DHEA and DHEAS. Double-immunohistochemical analysis of HSD3B2 and CYB5A in the normal adrenal glands identified a small number of cells where these two proteins overlap at the interface of the zonae fasciculata and reticularis, which might be responsible for the adrenal AD and T synthesis 30 . Comparison between age groups in this study showed that the co-localization of HSD3B2 and CYB5A is most prominent in the 13–20 year-old group, following adrenarche.…”
Section: Discussionmentioning
confidence: 98%
“…In the normal adrenal gland, HSD3B2 and CYB5A are segregated to the zonae glomerulosa and fasciculata or the zona reticularis, respectively, such that the major adrenal C 19 steroids are DHEA and DHEAS. Double-immunohistochemical analysis of HSD3B2 and CYB5A in the normal adrenal glands identified a small number of cells where these two proteins overlap at the interface of the zonae fasciculata and reticularis, which might be responsible for the adrenal AD and T synthesis 30 . Comparison between age groups in this study showed that the co-localization of HSD3B2 and CYB5A is most prominent in the 13–20 year-old group, following adrenarche.…”
Section: Discussionmentioning
confidence: 98%
“…This enzymatic distribution favors the synthesis of DHEA, with limited production of the downstream C 19 steroids A4 and T. Adrenal DHEA is then efficiently sulfonated to DHEAS by the sulfotransferase 2A1 (SULT2A1), making DHEAS by far the dominant adrenal-derived C 19 steroid. It has been proposed that A4 and downstream C 19 steroids are synthesized at the interface between the zona fasciculata and zona reticularis [3]. The androgenic synthetic capacity of the adrenal gland might be further amplified if the typical zonation and segregation of HSD3B2 and b5 are disrupted, as we have observed in patients with (CAH) [5].…”
Section: The Adrenal Cortex As a Source Of Androgensmentioning
confidence: 65%
“…The efficient synthesis of DHEA requires the cofactor protein cytochrome b 5 (CYB5A, b5), which greatly enhances the 17,20-lyase activity of 17α-hydroxylase/17,20-lyase (P450 17A1), and the conversion of DHEA to A4 utilizes the enzyme 3β-hydroxysteroid dehydrogenase type 2 (HSD3B2) in the adrenal. While these two proteins are co-expressed in the testicular Leydig cells and the ovarian theca cells, they are segregated in separate zones in the adrenal cortex: HSD3B2 in the zonae glomerulosa and fasciculata and b5 in the zona reticularis [3, 4]. This enzymatic distribution favors the synthesis of DHEA, with limited production of the downstream C 19 steroids A4 and T. Adrenal DHEA is then efficiently sulfonated to DHEAS by the sulfotransferase 2A1 (SULT2A1), making DHEAS by far the dominant adrenal-derived C 19 steroid.…”
Section: The Adrenal Cortex As a Source Of Androgensmentioning
confidence: 99%
“…As discussed in (Russell D. Romeo, 2010aRomeo, , 2010b, it is still unknown how adrenal function is developing during adolescence and how this is affected by stress. Nevertheless, based on human literature, we know that there is a general thickening of the adrenal cortex during this life epoch, which has been mostly studied in association to pubertal changes in sex hormones (Hui et al, 2009;Nakamura et al, 2015), while relevance for stress response remains unresolved.…”
Section: Hpa Axis Regulationmentioning
confidence: 99%